Analysis of Dispensing and Utilization Patterns of Medical Cannabis Products in State Licensed Cannabis Dispensaries - Tanco, Kimberson; Olson, Amanda; Fellman, Bryan; Jankowski, Mika; Lai, Stephen Y; Shete, Sanjay; Harbison, Kevin; Scheid, Jennifer; Bruera, Eduardo (Journal of palliative medicine, 2023)
To understand real-world dispensing and utilization patterns of medical cannabis (MC) and its financial impact on patients, we analyzed the database of a cannabis company licensed in New York state. To evaluate the tetrahydrocannabinol (THC)/cannabidiol (CBD) dose ratios, association of various medical conditions to THC/CBD dose, and the cost of products in registered patients receiving MC from four licensed state dispensaries. Retrospective analysis conducted on anonymized data between January 1, 2016 and December 31, 2020 listing 422,201 dispensed products from 32,845 individuals aged 18 years and older. Adult patients with medical certification for cannabis use in New York, USA. The database included patient's age, gender, qualifying medical condition, type and dose of product, medication directions, and amount of product dispensed. Findings showed a median age of 53 years with 52% of patients female. Males were found to use more products than females (1.06:1). Pain (85%) was the most common medical condition and inhalation (57%) the most common route except when used for cancer-directed treatment and neurological conditions. Individuals received a median of six prescriptions costing a median of $50/product. Average THC:CBD ratios were 28:0.5 mg/day and 12:0.25 mg/dose. Neurological conditions demonstrated the highest average cost [mean (95% confidence interval CI): $73 ($71-$75)] and average CBD/dose per product [mean (95% CI): 5.89 (5.38-6.40)]. Individuals with a history of substance use disorder utilizing MC as an alternative substance displayed the highest average THC/dose [mean (95% CI): 14.25 (13.36-15.14)]. MC was utilized for various medical conditions with variability in THC:CBD ratio seen depending on the condition. Cost variation was also observed based on the individual's medical condition.